Characterization of copper microelectrodes, following a homemade lithography, technique, and gold electroless deposition - Rodríguez Martínez, Marco Antonio (2016)
We report the fabrication and characterization of copper microelectrodes obtained by a homemade lithography technique and after gold electroless deposition. For the fabrication, planes consisting of arrays of electrodes (black in color) with bow tie shape were designed and printed on a transparent paper (Canson ltd.). Using an embroidery frame with a silk fabric, a photographic emulsion was spread on the silk and simultaneously pressing the Canson paper on it. The system was introduced into a closed box and exposed with a UV light. The designed electrode templates prevented direct exposition of the UV light over copper films and indelible ink was spread over it. After the ink was dried, the copper film is immersed into ferric acid to attack the uncovered copper parts (where there is no ink). In this way, we obtained copper electrodes with initial gap separation of ~142μm and subsequently, they followed electroless deposition of gold to make the copper electrodes to contact. For the characterization, electrical measurements were performed. They present ohmic resistance values in the order of 106 Ω produced by surface scattering of the electrons within the gold microwire and enhanced by oxidation of the copper electrodes.